Repetitions to failure increase pectoralis major activation with similar neuromuscular fatigue in trained men - Gomes, M. C.; Lacerda, L. T.; Gurgel Simões, M.; Ribeiro Diniz, R. C.; Heleno Chagas, M.; Lima, F. V. (Journal of Physical Education, 2020)
Resistance training protocols performed to muscle failure (MF) have been employed in an attempt to maximize activation and neuromuscular fatigue. Therefore, the aim of this study was to compare the surface electromyography amplitude (EMGRMS) and frequency (EMGFREQ) of the pectoralis major between protocols performed to MF and non muscle failure (NMF). Seven trained men performed three sets at 60% of a repetition maximum, with a 3 min rest period and a 6s repetition duration. MF protocol was performing with maximum number of repetitions in all sets, while in NMF protocol subjects performed 6 repetitions in 3 sets. For data analysis two two-way repeated measures ANOVAs (Protocol x Repetition) were used and when necessary, Bonferroni post hoc was performed. The EMGRMS was higher in the protocol MF compare to NMF, but there was no difference in EMGFREQ between protocols. Although there were no significant differences in the frequency domain between protocols, perform repetitions to MF was a determining factor to generate higher amplitude of the electromyography signal. Thus, perform repetitions to MF could be considered an effective strategy to increase muscle activation in trained individuals, however, with similar neuromuscular fatigue.